The Impact of Interactive Reading Using Local Folktales Stories in Supporting Students’ Vocabulary Achievement in Indonesian EFL Learners - Ismail, Ismail (Maspul Journal of English Studies, 2019)
The big significant problem associated with the major foreign language is always influenced by teachers and students are the mastery of vocabulary. This study was designed to reconnoiter if a reading local folktales story was helpful for students’ English vocabulary at the second year students of SMA Muhammadiyah Kalosi-Enrekang. The research design used is classroom action research which is expected to illustrate the application of reading folktales to improve students’ vocabulary that comprised of two cycles, and in every cycle consisted of four stages. The subject in this research was class X-B in 2015-2016 academic years with 30 students. The test was administered to examine the impacts of interactive reading of Enrekang folktales stories toward students’ vocabulary achievement. Results published that the impact of reading the stories of the local folktales on vocabulary instruction is determined by comparing the performance of the participants in the D-test, test in cycle 1 and cycle 2, and a questionnaire after cycle 2. Reading local folktales is a potential activity to improve the students’ vocabulary. The questionnaire results also clarified the students’ attitude toward folktales technique as vocabulary instruction was favorable. This can be approved to the effect of using local folktales stories on increasing vocabulary performance of learners. The usage of folklore stories offers authentic reading resources which give the students a chance to intermingle with the text emotionally and involve themselves personally. In reply to this situation, teachers and students always developing and searching for manners to improve reading and vocabulary instruction.